Methodology for adjusting GPRA Workforce Development Program performance targets for the effects of business cycles - Timothy J. Bartik; Randall W. Eberts; Wei-Jang Huang (W.E. Upjohn Institute for Employment Research, 2009)
The U.S. Department of Labors Employment and Training Administration issued Training and Employment Guidance Letter (TEGL) 09-08 Change 1 on June 5, 2009. This guidance letter revises the Government Performance and Results Act (GPRA) performance measures for federal workforce development programs to take into account the effect of the recession on participants labor market and educational outcomes. As described in the TEGL, the performance targets of the various workforce development programs have been developed for use for the years PY2008 through PY2010. They are intended to be used for PY2009 performance target negotiations and will appear in the Presidents Budget Request for FY2010. The performance targets for future program years, adjusted for unemployment rates, are driven by the economic assumptions of the Presidents Budget Request for FY2010. The revised performance targets are based on analysis carried out as part of a study conducted for the U.S. Department of Labor by the W. E. Upjohn Institute for Employment Research. This working paper has two purposes. The first is to describe the methodology used to estimate the relationship between unemployment rates and workforce program performance targets. The second is to describe the procedures used to adjust the GPRA performance targets for changes in unemployment rates during the current recession and over the business cycle. The study described in this working paper is the initial phase of an ongoing analysis of the effect of economic conditions on workforce development program outcomes.
Keywords: J24; J68; 330